Synthesis of Polylactic Acid (PLA) by Polycondensation Method - Horváth, Tibor; Szabó, Tamás József; Marossy, Kálmán (International Journal of Engineering and Management Sciences, 2020)
The Polylactic acid (PLA) is compostable and natural renewable sourced plastic type. Its mechanical properties quite similar to the PET, therefore the PLA is a good alternative for strongly ruled food industrial application. The PLA only has one critical attribute – the relatively low glass transition temperature. According to the relevant literature the glass transition of PLA is in the range of 40-70°C. In light of this fact, this material can be used only in that segments of food industrial field where the packaging process temperature are under of the lower limit of Tg range. The actual Tg of a material is highly depends on the molar mass and material structure, therefore the molar mass and the structure of material should be designed according to the future requirements of application and procedures.